Big data and open data in education, evaluation of the scope of existing initiatives: case study Faculty of Technology and Applied Sciences of the National University of Catamarca - Herrera, Claudia M. (2022)
Data is the fuel of the 21st century. Increasingly our economies are driven by this input. Data has the potential to create social value, something that higher education institutions are beginning to rely on, as evidenced by the initiatives of public access to their data and the various advantages and benefits provided by big data in improving educational management, the development of customized curricula, monitoring the academic performance of students, as well as in the generation of digital repositories that are the product of years of academic, teaching and research activity. The present research aims to evaluate the scope of existing initiatives on the subject of Big Data and Open Data in education, in the Faculty of Technology and Applied Sciences of the National University of Catamarca (UNCA), producing an effective contribution with preliminary results for the research project called "ICT in the Service of Open Data: Current Situation, Conceptualization and Initiatives for Opening Public Information" which is being carried out in the Department of Informatics.